Efektivitas Media Pembelajaran Digital Berbasis Canva terhadap Minat Belajar PAI Siswa Sekolah Dasar - Indrawan, Muhammad Irham; Zahratussalsah, Dihya; Kurniawan, Nasty; Tafaddal; Mahfuza, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the utilization of Canva-based digital learning media in improving elementary school students’ interest in learning Islamic Religious Education (PAI). The development of educational technology requires teachers to present learning media that are attractive, interactive, and suitable for students’ characteristics. One of the digital media that can be used is Canva, a graphic design application that provides various visual learning features. This study employed a quantitative research method with library research approach. The subjects of this study were elementary school students in Islamic Religious Education classes. Data collection techniques included observation, questionnaires, and documentation. The data were analyzed using quantitative descriptive techniques to determine students’ learning interest before and after the implementation of Canva-based learning media. The results are expected to show that the use of Canva-based digital learning media can improve students’ learning interest because the learning materials are presented in a more attractive, understandable, and interactive way. Therefore, Canva can be an effective alternative digital learning media in Islamic Religious Education learning at the elementary school level.